Antiphospholipid antibodies in patients with lupus nephritis: clinical correlations and associations with long-term outcomes. (October 2019) - Yap, D Y H; Thong, K M; Yung, S; Tang, C; Ma, B M Y; Chan, T M
Whether the presence or absence of antiphospholipid antibodies (aPL) in patients with lupus nephritis (LN) is associated with differences in clinical outcomes remains unclear. We reviewed LN patients at a single centre during 2000–2017, and compared the clinical features and long-term outcomes between patients who were seropositive or seronegative for aPL. aPL was detected in 53/149 (35.6%) patients with biopsy-proven LN, and anticardiolipin IgM, anticardiolipin IgG, anti-β2 glycoprotein I and lupus anticoagulant was detected in 18.8%, 18.1%, 10.7% and 8.1%, respectively. Follow-up was 155.8 ± 61.0 months, and was similar between aPL-seropositive and -seronegative patients. aPL seropositivity persisted in 94.3% of patients during remission. aPL-seropositive patients showed inferior patient survival (91% and 85% at 10 and 15 years, respectively, compared to 99% and 95% in aPL-seronegative patients; p  = 0.043). Nine (6.0%) patients died during follow-up, including six aPL-seropositive (four thrombotic events and two bleeding complications related to anticoagulation) and three aPL-seronegative patients. aPL seropositivity was associated with more rapid decline in estimated glomerular filtration rate (–1.44 mL/min/year compared to –0.38 mL/min/year in aPL-seronegative patients; p  = 0.027) and inferior long-term renal survival (82% and 74% at 10 and 15 years, respectively, compared to 91% and 87% in aPL-seronegative patients; p  = 0.034). aPL-seropositive patients also had a higher incidence of thrombotic events and miscarriage (32.1% and 13.2%, respectively, compared to 16.7% and 2.1% in the aPL-seronegative group; p  = 0.030 and 0.006). We concluded that aPL seropositivity was associated with inferior long-term patient and renal survival and more frequent thrombotic events and miscarriage in LN patients.